2011
DOI: 10.1002/jat.1629
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity studies of nonylphenol and octylphenol: hormonal, hematological and biochemical effects inClarias gariepinus

Abstract: Among the numerous chemicals discharged into aquatic ecosystems, nonylphenol (NP) and octylphenol (OP) have been shown to have a potent effect on the endocrine system of fish; this issue has been clearly dealt with in several studies. The objective of this study was to assess and compare the general toxicity of these estrogenic chemicals individually on Clarias gariepinus. Fish were exposed to different concentrations of both NP and OP (250, 500, 750 and 1000 μg l(-1) ) under semi-static conditions for a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 68 publications
4
18
0
Order By: Relevance
“…Therefore, these chemicals through cortisol induction could modulate intermediary metabolism and modify energy metabolism in fish (Mommsen et al, 1999). Senthil Kumaran et al (2011) stated that glucose elevation after exposure to nonylphenol and octylphenol in African catfish (Clarias gariepinus) may be the result of increased synthesis of adrenocorticotropic hormone and glucagon and reduced synthesis of insulin. As a result, glycogen stored in the liver is converted to glucose leading to an increase in blood glucose level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these chemicals through cortisol induction could modulate intermediary metabolism and modify energy metabolism in fish (Mommsen et al, 1999). Senthil Kumaran et al (2011) stated that glucose elevation after exposure to nonylphenol and octylphenol in African catfish (Clarias gariepinus) may be the result of increased synthesis of adrenocorticotropic hormone and glucagon and reduced synthesis of insulin. As a result, glycogen stored in the liver is converted to glucose leading to an increase in blood glucose level.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma biochemical constituents, thyroid hormones, liver function enzymes and ionoregulatory endpoints could also be used as biomarkers to reflect the toxicity of chemicals as they have been frequently used for the toxicity assessment of other PAHs in fish and other animals (Alonso-Alvarez et al, 2007;Kim et al, 2008;Latif et al, 2014;Maria et al, 2002;Okwu et al, 2014;Osman et al, 2009;Salman, 2011;Tintos et al, 2008;Wegwu and Omeodu, 2010). Plasma biochemical indicators and transaminases have been proved to be suitable stress biomarkers in fish because they are inexpensive, less variable, more highly conserved between species and are easy to measure (Naderi et al, 2015;Senthil Kumaran et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…During stress condition fish may mobilize protein to meet energy demand to maintain increased physiological activity [72]. Blood and structural proteins and carbohydrate reserves may convert to energy under stress condition leading to a significant decrease in serum protein concentrations [73]. Hyproteinemia in toxicant stressed animals indicate a generalized response to any stress.…”
Section: Parameters Control Experimentsmentioning
confidence: 99%
“…However, several investigations have reported that the unstable property of APEs in environment cause rapid degradation to hydrophobic and more toxic alkylphenols including 4-nonylphenol (4-NP) and 4-t-OP. Based on hematological and biochemical parameters examined, the study elucidated that OP had a relatively greater effect than NP and affected hematological enzymes leading to serious impairment of the metabolism and physiology in African sharptooth catfish (C. gariepinus) [25]. Other study reported that zebrafish embryos exposed to 1 µM of 4-t-OP developed normally [26], however our results showed that zebrafish exposure to 1 µM of 4-t-OP resulted in cardiovascular defect.…”
Section: Discussionmentioning
confidence: 53%